The Role of Islamic Religious Education in Overcoming Students’ Moral Degradation (A Case Study at SDN 122 Cijawura Bandung) - Siti Sadiah; Yunita Eka Putri; Azqya Inayah Ummu Abdullah; Fitri Aini Latifah; Amara Kovács (International Journal of Post Axial: Futuristic Teaching and Learning, 2025)
Moral degradation among elementary school students is a growing concern in the digital and globalized era. Behaviors such as declining respect for teachers, poor discipline, and reduced social empathy reflect a weakening internalization of moral values. This study aims to describe the forms of moral degradation observed among students at SDN 122 Cijawura Bandung and to analyze the strategic role of Islamic Religious Education (PAI) in addressing these issues. The research uses a qualitative case study approach, with data collected through in-depth interviews, observations, and documentation. The findings reveal that PAI plays a vital role in character development through an integrative approach encompassing cognitive, affective, and psychomotor domains. PAI teachers act as role models, facilitators, and spiritual mentors by employing contextual teaching methods, organizing religious activities such as Qur'an recitation and congregational prayers, and reinforcing moral values through daily interactions. Despite challenges such as limited instructional time and the pervasive influence of unsupervised digital media, the strategies implemented by teachers show a gradual positive impact on students’ behavior. The study recommends fostering synergy between schools, teachers, and parents to build an educational ecosystem that supports the development of noble character from an early age.